2017
DOI: 10.1016/j.media.2017.07.001
|View full text |Cite
|
Sign up to set email alerts
|

Gyral net: A new representation of cortical folding organization

Abstract: One distinct feature of the cerebral cortex is its convex (gyri) and concave (sulci) folding patterns. Due to the remarkable complexity and variability of gyral/sulcal shapes, it has been challenging to quantitatively model their organization patterns. Inspired by the observation that the lines of gyral crests can form a connected graph on each brain hemisphere, we propose a new representation of cortical gyri/sulci organization pattern – gyral net, which models cortical architecture from a graph perspective, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 68 publications
0
21
0
Order By: Relevance
“…Besides the morphologies of lobes and gyro-sulcal patterns, other factors could have a close relationship with 3-hinge numbers and shape patterns. For example, in one of our recent studies (Ge et al, 2017), denser dMRI derived fiber connections were found in 3-hinges than other gyral regions. Such a relationship leads to a hypothesis that axonal growth might play a role in 3-hinge formation.…”
Section: Discussion S a N D C Onc Lu Sion Smentioning
confidence: 77%
See 4 more Smart Citations
“…Besides the morphologies of lobes and gyro-sulcal patterns, other factors could have a close relationship with 3-hinge numbers and shape patterns. For example, in one of our recent studies (Ge et al, 2017), denser dMRI derived fiber connections were found in 3-hinges than other gyral regions. Such a relationship leads to a hypothesis that axonal growth might play a role in 3-hinge formation.…”
Section: Discussion S a N D C Onc Lu Sion Smentioning
confidence: 77%
“…The locations and the morphological skeletons of 3-hinges were extracted based on our recently developed automatic pipeline (Chen et al 2017), which is illustrated in Figure 2. To make the manuscript self-contained, we present a summarized version of this pipeline.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations